2020
DOI: 10.3390/su12072874
|View full text |Cite
|
Sign up to set email alerts
|

Soil Recovery Assessment after Timber Harvesting Based on the Sustainable Forest Operation (SFO) Perspective in Iranian Temperate Forests

Abstract: Minimizing the impact of timber harvesting on forest stands and soils is one of the main goals of sustainable forest operation (SFO). Thus, it is necessary to make an accurate assessment of forest operations on soil that is based on the SFO perspective. The present study was conducted according to SFO principles to investigate the time required for the natural recovery of soil after disturbance by skidding operations in some Iranian forests. The physical, chemical, and biological properties of soil found in ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…These studies demonstrate that in the evaluation of skid trail recovery, it is prudent to measure multiple soil properties to ascertain if the recovery is complete. Another aspect of skid trail recovery that has received less attention than physical properties is the rehabilitation of chemical properties (Ebeling et al 2017;Neaves et al 2017;Ilintsev et al 2018;Warlo et al 2019;Sohrabi et al 2020). In Malaysia, Malmer et al (1998) encountered contrasting results in two skid trails that were in close proximity to each other (500 m).…”
Section: Soil Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrate that in the evaluation of skid trail recovery, it is prudent to measure multiple soil properties to ascertain if the recovery is complete. Another aspect of skid trail recovery that has received less attention than physical properties is the rehabilitation of chemical properties (Ebeling et al 2017;Neaves et al 2017;Ilintsev et al 2018;Warlo et al 2019;Sohrabi et al 2020). In Malaysia, Malmer et al (1998) encountered contrasting results in two skid trails that were in close proximity to each other (500 m).…”
Section: Soil Recoverymentioning
confidence: 99%
“…In research between 20 to 25 years after logging operations there is a contrast when comparing results of studies evaluating bulk density (BD) or soil penetration resistance (PR). For example, three studies that evaluated BD and PR in skid trails 20 to 25 years old, at a depth of 0-10 cm, found no complete soil recovery for these soil properties (Pennington et al 2004;Sohrabi et al 2019;Sohrabi et al 2020). However, three other studies of similarly-aged skid trails that were measured at a depth of only 0-5 cm (Neaves et al 2017;DeArmond et al 2019) and 5.1 cm (Froehlich et al 1985) found a recovery of BD at these depths.…”
Section: Soil Recoverymentioning
confidence: 99%
“…After compaction, for recovery processes of soil features may be needed from a few years to multiple decades to return to the pre-harvest levels, as documented in the previous studies [5,7,9,11,12]. One important issue to accelerate the recovery processes of soil properties and rehabilitate soil quality on areas affected by different degree of compaction is seedling planting [4,9,13].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, soil compaction imposed by heavy machines during logging operations may dramatically affect the balancing and regulation of forest productivity process by demolishing soil structure and impairing soil physical properties [5]. Consequently, this phenomena lead to reduce the porosity in soil volume [6,7], decrease the connectivity of pore spaces [8,9], increase soil bulk density and strength [10,11], and reduce water infiltration and gas exchange [12,13], with consequent negative influences on soil macro-and micro-organisms (e.g., earthworms and microarthropods) [7,9], and elongation of root systems [14] and, ultimately, reducing tree and seedlings growth [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the laboratory, soil samples were dried in an oven at 105 • C for 24 h until reaching a constant mass to determine the soil moisture content, dry bulk density, and porosity. Soil texture was determined using a hydrometric method [55].…”
Section: Measurements and Laboratory Analysismentioning
confidence: 99%